AB0148 Histone deacetylase inhibitors prevent inflammation-mediated inactivation of the forkhead box class o transcription factor FOXO1 in rheumatoid arthritis. (23rd January 2014) - Grabiec, A.M.; Hartkamp, L.M.; van Baarsen, L.G.M.; Korchynskyi, O.; Tak, P.P.; Reedquist, K.A.
Abstract : Background: Reversible acetylation is an important post-translational mechanism regulating activity and nuclear retention of many transcription factors, including forkhead box O (FoxO) proteins. FoxOs integrate environmental signals to modulate the expression of genes regulating inflammatory responses, cell cycle and apoptosis. Enhanced inactivation of FoxOs has been reported in the synovial tissue of patients with rheumatoid arthritis (RA) compared to disease controls. Objectives: To examine the relationship between inflammation and FoxO expression and activity in RA, determine the effects of histone deacetylase inhibitors (HDACi) on FoxO expression and activity in RA fibroblast-like synoviocytes (FLS), and identify gene products relevant to RA regulated by FoxO proteins in RA FLS. Methods: Total RNA was isolated from synovial biopsies obtained by arthroscopy from 20 RA patients. FoxO1, FoxO3a, FoxO4, TNFα, MMP-1 and IL-6 expression were measured by quantitative PCR (qPCR) in synovial tissue and RA and osteoarthritis (OA) FLS. RA FLS were stimulated with IL-1β or TNFα, in the absence or presence of the HDACi trichostatin A or ITF2357, and FoxO family member expression and FoxO1 DNA binding activity were measured by qPCR and ELISA-based assays, respectively. RA FLS were transduced with adenovirus encoding control GFP or constitutively active FoxO1ADA to examine the effects on gene expression using qPCR arrays. Results: Negative correlations were observed between RA synovial tissue expression of FoxO1 and the levels of serum C-reactive protein (CRP) ( R = -0.771, P =0.0008), erythrocyte sedimentation rate (ESR) ( R = -0.739, P =0.0003), and disease activity score 28 (DAS28) ( R = -0.575, P =0.01). A strong negative correlation was also observed between synovial FoxO1 and IL-6 mRNA levels ( R = -0.628, P =0.004), but not TNFα or MMP-1. FoxO1, FoxO3a and FoxO4 mRNA were each detected in RA and OA FLS, and FoxO1 mRNA levels were significantly reduced in RA FLS compared to OA FLS ( P <0.05). IL-1β and TNFα significantly suppressed FoxO1 DNA binding activity in RA FLS, and selectively downregulated FoxO1 mRNA expression in a time-dependent manner. HDACi reversed IL-1β-mediated reduction of FoxO1 DNA binding and mRNA expression. Overexpression of FoxO1ADA in RA FLS suppressed expression of antiapoptotic Bcl-XL, and enhanced expression of proapoptotic Bim and the cell cycle inhibitor p27 Kip1, and this effect was associated with reduced cell viability. FoxO1 activation had dual effects on IL-1β-mediated induction of inflammatory mediators: while expression of CCL2, CXCL6, PDGF and ICAM1 was reduced, mRNA of CXCL3, IL-8 and BMP-2 were elevated in FLS expressing constitutively active FoxO1. Conclusions: We demonstrate that inflammatory stimuli decrease FoxO1 expression and DNA binding activity, effects reversed by exposure of RA FLS to HDACi. Restoration of FoxO1 activity suppresses a subset of genes regulated by HDACi during FLS activation, indicating that enhancing FoxO1 function might be one of the mechanisms by which HDACi mediate their anti-inflammatory effects in RA synovial cells. Our findings also suggest that cytokine-mediated inactivation of FoxO1 might promote proliferation and survival of stromal cells in the inflamed joint in RA. Disclosure of Interest: None Declared